2018
DOI: 10.1111/ijpp.12453
|View full text |Cite
|
Sign up to set email alerts
|

Weight management counselling among community pharmacists: a scoping review

Abstract: Obesity has a significant impact on the health and wellness of adults globally. Recent research has shown that community pharmacies have the potential to positively impact patient weight loss. However, additional research is needed into the specific interventions that bring the most value to patients and can be sustained and spread across community pharmacy practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…It has been shown that pharmacist involvement in the dispensing of naloxone had significant reductions in fatal opioid overdoses as opposed to just improving access [56]. Other wellness and prevention services include weight management, fluoride treatments, falls prevention, pharmacogenomics, sleep assessment, drug take back, nutraceuticals, and bioidentical hormone replacement [57,58,59,60,61,62]. Lastly, community-based pharmacist practitioners are involved in providing Medicare Annual Wellness Visits in physician offices [63].…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that pharmacist involvement in the dispensing of naloxone had significant reductions in fatal opioid overdoses as opposed to just improving access [56]. Other wellness and prevention services include weight management, fluoride treatments, falls prevention, pharmacogenomics, sleep assessment, drug take back, nutraceuticals, and bioidentical hormone replacement [57,58,59,60,61,62]. Lastly, community-based pharmacist practitioners are involved in providing Medicare Annual Wellness Visits in physician offices [63].…”
Section: Resultsmentioning
confidence: 99%
“…This proportion was similar to other weight management programs in the community pharmacy. 17 A previous pilot study in Australian community pharmacies showed that 32% of participants achieved a weight loss of 5% after three months of follow-up. 18 In another study, carried out in community pharmacies in the UK, around a quarter of the patients included in the intervention achieved 5% reduction in body weight at 3 months.…”
Section: Discussionmentioning
confidence: 98%
“…According to a previous scoping review, 17 weight management programs carried out in community pharmacies have until now been centered on behavioral counselling given to the patients. However, none of them have included in the intervention the evaluation of other chronic diseases and optimization of medication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen articles were obtained and summarized (Table 1). [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] In the past 10 years, most of the literature on pharmacy-led obesity management comes from community pharmacy initiatives worldwide (U.S., U.K., Spain, Australia, and Thailand) to implement weight-loss or weight-management programs as a service to the community. Most of the interventions used were pre/post studies to determine the effect of the pharmacist-led service.…”
Section: Clinical Pharmacists' Intervention In the Literaturementioning
confidence: 99%